Findings of Persistent Scatterer Interferometry (PSI) for Vilnius area, Lithuania - Čyžienė, Jolanta; Graniczny, Marek; Kowalski, Zbigniew; Piotrowski, Andrzej; Satkūnas, Jonas; Wasowski, Janusz (Journal of Environmental Engineering and Landscape Management, 2010)
Ground surface deformations can be related to natural and anthropogenic activities. The availability of ground movement data from regular satellite observations, combined with the knowledge of local geology and geomorphology, can help to improve our understanding of subsidence and soil geotechnical settlement phenomena, as well as to distinguish them from structural deterioration of buildings, which in urban environments represent the most common type of radar targets (PS). In Lithuania ground surface deformations are usually related to landslides, karstic, suffusion processes and anthropogenic activities (particularly in urban areas), which can trigger destruction of buildings, communication life‐lines and soil consolidation. This paper is intended to illustrate considerable interpretative difficulties concerning the Persistent Scatterers Interferometry (PSI) results from synthetic aperture radar (SAR) data acquired over the Vilnius area (Lithuania) in the framework of TERRAFIRMA project. Protection of groundwater from pollution in the face of both man's intervention and geologically‐driven movements is a high priority for the City Authorities. The distribution of numerous PS shows evidence of the spatial variability of the ground conditions throughout the old town and adjacent area of Vilnius. PS detected in the centre of Vilnius are characterized by velocities mainly ranging between –1.5 to +1.5 mm/year during about 8.5 years of observation. These figures are within the measurement precision error and imply a general stability of the city centre. Nevertheless, the review of the PS dataset has enabled to identify several sites within the Vilnius area characterized by spatially consistent concentrations of the downward moving PS. The localities as well as the site of the PS reference point were checked during the field reconnaissance and the implications of PS results are discussed in this paper.Article in English.Vilniaus ir jo apylinkių interferometrinių matavimų duomenų analizės rezultataiSantrauka. Žemės paviršiaus pokyčius sukelia nuošliaužos, žemės drebėjimai, potvyniai, kranto erozija, gruntų sėdimas, kurį lemia požeminio vandens išsiurbimas ir požeminis naudingųjų iškasenų eksploatavimas, požeminės karstinių tuštumų įgriuvos ir kitos priežastys. Duomenys apie žėmės paviršiaus pokyčius tam tikroje vietoje, gauti atlikus palydovinius stebėjimus, kartu su geologiniais ir geomorfologiniais duomenimis apie tiriamąją vietovę gali padėti nustatyti žemės paviršiaus grimzdimo reiškinius. Lietuvoje žemės paviršiaus pokyčius daugiausiai sukelia nuošliaužos ir karstinės įgriuvos, dėl kurių dažnai sugriūva pastatai ir komunikacijos. Analizuojami Vilniaus ir jo apylinkių palydovinės interferometrijos (SAR) duomenys ir aptariamos problemos, su kuriomis teko susidurti juos interpretuojant. Preliminari duomenų analizė rodo, kad Vilniaus ir jo apylinkių žemės paviršius gana stabilus, kasmetinis žemes paviršiaus judesių greitis svyruoja nuo –1,5 iki +1,5 mm/metus. Pavienėse Vilniaus teritorijose užfiksuotos ir anomalios neigiamos grimzdimo reikšmės. Šių reikšmių atitiktis vietovėje buvo tikslinama lauko darbų metu. Išsamiai aprašomi tyrimo rezultatai.Reikšminiai žodžiai: nuotoliniai palydoviniai tyrimai, radaro sintetinė apertūra, interferometrija, nuolatinės sklaidos taškai, nuošliaužos, Vilnius, Lietuva.Анализ и результаты интерферометрических измерений на территории города Вильнюса и его окрестностейРезюме. Оползни, землетрясения, наводнения, береговая эрозия, оседания грунта из-за откачивания подземных вод и эксплуатации подземных полезных ископаемых, а также обвалы подземных карстовых пустот и другие причины изменяют земную поверхность. Данные об изменениях земной поверхности в различных местностях, полученные по результатам сателлитных наблюдений, совместно с геологическими и геоморфологическими исследованиями изучаемой местности могут помочь установить явления погружения земной поверхности. Изменения земной поверхности в Литве в основном связаны с оползнями и карстовыми обвалами, часто разрушающими здания и коммуникации. В статье обсуждается проведенный анализ данных сателлитной интерферометрии (SAR) на территории города Вильнюса и его окрестностей, а также проблемы, с которыми пришлось столкнуться при интерпретации этих данных. Предварительный анализ данных показывает, что земная поверхность территории города Вильнюса и его окрестностей достаточно стабильна, ежегодная скорость движения земной поверхности колеблется от −1,5 до +1,5 мм/год. Однако на некоторых участках города Вильнюса наблюдаются и аномальные отрицательные значения. Точки с такими значениями проверялись на местности во время проведения полевых работ, а результаты исследования детально описаны в настоящей статье.Ключевые слова: дистанционные спутниковые исследования, синтетическая апертура радара, интерферометрия, точки постоянного рассеяния, оползни, Вильнюс, Литва.First Publish Online: 10 Feb 2011